Egg Spots Are Important Cues for Egg Recognition in Barn Swallows - Kui Yan; Jinmei Liu; Kangning Luo; Wei Liang (Ecology and Evolution)
ABSTRACT Egg recognition is one of the most common strategies utilized by host birds to combat brood parasitism. Eggshell surface features (e.g., eggshell color and spots) are important cues for host egg recognition, enabling avian hosts to recognize and reject foreign eggs. The barn swallow (Hirundo rustica), as one host of the common cuckoo (Cuculus canorus), has demonstrated variation in their egg rejection propensity geographically. However, it remains unclear whether eggshell spots play an important role in their egg recognition. To this end, this study examined the role of eggshell spots in egg recognition in two populations of barn swallows. Our results revealed that in both Danzhou and Dongfang populations, the rejection rate of barn swallows for spotted eggs was significantly lower than that for eggs without spots, suggesting that eggshell spot signaling plays a pivotal role during the process of egg recognition in barn swallows. Our findings also indicated that egg shape (ovoid vs. round) did not affect egg recognition by barn swallows. This was most likely because the round shape did not deviate significantly from egg‐shaped properties, causing the inability of barn swallows to distinguish the difference in shape.